Rapid judgment method for limestone mineral powder

By combining XRD and XRF technologies, the limestone ore powder is rapidly tested, which solves the problem of long-term and low accuracy in the existing technology, and achieves rapid and accurate supervision of the quality of ore powder, ensuring the stability of the quality of the asphalt mixture.

CN119619198APending Publication Date: 2025-03-14NANJING FORESTRY UNIV

Patent Information

Application Number
CN202311189333.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

At this stage, the method of detecting limestone powder is time-consuming, low efficiency, low accuracy, and lacks effective quality supervision, resulting in large fluctuations in the quality of ore powder and affecting the quality of asphalt mixture.

Method used

X-ray diffraction technology (XRD) and X-ray fluorescence analysis technology (XRF) are combined, and X-ray fluorescence analysis technology (XRF) are used to test the ore powder sample to be tested, diffraction spectrum and fluorescence spectrum are obtained, and digital image processing is carried out to determine the elemental composition, chemical composition, mineral composition and relative mass percentage of the ore powder, and to judge the lithologic and quality of the processed rocks.

Benefits of technology

It realizes rapid and accurate detection of limestone powder, which consumes short time and is efficient, can effectively supervise the quality of ore powder and ensures the stable quality of asphalt mixture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119619198A_ABST
    Figure CN119619198A_ABST
Patent Text Reader

Abstract

The invention discloses a rapid detection method of limestone mineral powder, and belongs to the technical field of road engineering material detection. The rapid detection method comprises the following steps: respectively acquiring a diffraction spectrum and a fluorescence spectrum of a mineral powder sample by using XRD and XRF scanning equipment and an image processing technology; determining mineral composition according to characteristic peaks in an actually measured diffraction spectrogram of the mineral powder sample, and calculating relative mass percent as an index for identifying whether the mineral powder sample is limestone mineral powder or not; the method comprises the following steps: carrying out comparative analysis on a characteristic peak in an actually measured fluorescence spectrum of a mineral powder sample and a standard fluorescence spectrum, and taking the relative mass percent of calcium oxide (CaO), magnesium oxide (MgO) and silicon dioxide (SiO2) in the mineral powder sample as an index for judging the quality of the mineral powder sample. According to the method, the property and the quality of the asphalt mixture mineral powder can be quickly and accurately judged, the operation is simple, effective supervision on the lithology of the rock processed by the limestone mineral powder is effectively realized, and a solid foundation can be laid for subsequently providing a limestone mineral powder quality grading method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of road engineering material detection, and in particular relates to a method for quickly distinguishing limestone mineral powder. Background Art

[0002] Limestone powder is a common filler in asphalt mixtures, which helps to improve the road performance of asphalt mixtures, reduce deformation and cracking of asphalt mixtures, and extend the service life of asphalt mixtures. my country's current "Highway Engineering Aggregate Test Procedure JTG F42-2005" has put forward clear requirements for the apparent relative density, water content, particle size range, appearance, hydrophilicity coefficient, plasticity index and heating stability of mineral powder for asphalt mixtures. Although the determination method of the above indicators is simple, the determination method of each indicator is different, and each indicator needs to be determined under specific test conditions, resulting in a long time and low efficiency in the quality detection of mineral powder. At the same time, the measurement results will have large errors and fluctuations due to too many manual operation steps.

[0003] my country's current "Highway Engineering Aggregate Test Code JTG E42-2005" requires that the mineral powder of asphalt mixture must be obtained by grinding water-repellent stone materials such as strong basic rocks in limestone or igneous rocks. Limestone mineral powder is currently widely used. However, since the existing relevant technical specifications do not make clear provisions on the product quality grade of limestone mineral powder, and there is a lack of effective supervision of the rock properties of mineral powder processing at the construction site, it is impossible to determine whether the mineral powder is indeed processed from limestone, resulting in large fluctuations in the quality of the mineral powder actually purchased, which affects the quality of asphalt mixture to a certain extent.

[0004] In the field of detection technology, X-ray diffraction technology (XRD) is a non-destructive detection technology that uses monochromatic X-rays to enter crystals to produce strong X-ray diffraction in certain special directions, thereby determining the crystal structure. It is fast, accurate, and efficient, and its applications are in many fields such as materials, chemistry, biology, medicine, ceramics, metallurgy, and minerals. X-ray fluorescence analysis (XRF) is a method that uses primary X-ray photons or other microscopic particles to excite atoms in the sample to be tested to produce fluorescence (secondary X-rays) to analyze the material composition and chemical morphology. It is also fast, accurate, and non-destructive. It is mainly used to determine the constituent elements of the material and their relative mass percentages; it is currently widely used in the composition analysis of various materials such as cement, metals, ores, petroleum, chemicals, and food in the industrial field. However, the above two rapid detection technologies have not yet been used in the field of highway engineering material detection, especially in the field of limestone mineral powder quality detection. Summary of the invention

[0005] The purpose of the present invention is to provide a method for quickly distinguishing limestone powder, so as to solve the problems that the standard method for detecting limestone powder at this stage is time-consuming, inefficient, and inaccurate, and its quality is difficult to be effectively supervised.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] Step 1: prepare a mineral powder sample to be tested, and use an XRD device to perform X-ray diffraction on the prepared mineral powder sample to be tested to obtain a diffraction spectrum.

[0008] Step 2: Perform digital image processing on the diffraction spectrum to determine the type and relative mass percentage of effective mineral components in the mineral powder sample to be tested through characteristic peaks.

[0009] Step 3: Use XRF technology to test the national standard material GBW03107A limestone sample and the mineral powder sample to be tested in turn to obtain the standard fluorescence spectrum and the measured fluorescence spectrum respectively.

[0010] Step 4: Perform digital image processing on the standard fluorescence spectrum and the measured fluorescence spectrum, compare and analyze the position of the characteristic peak and the change of fluorescence intensity, obtain the main element composition of the measured mineral powder sample, and use the main measurement parameters of the corresponding elements to determine the corresponding chemical composition and its relative mass percentage.

[0011] Step 5: Using the measured effective mineral components and their relative mass percentages of the mineral powder sample to be tested as indicators, determine the lithology of the processed rock of the mineral powder according to the determination criteria.

[0012] Step 6: Compare and analyze the chemical composition and relative mass percentage of the measured main elements of the mineral powder sample to be tested with the corresponding indicators of the standard limestone sample, and judge the quality of the mineral powder sample to be tested according to the standard regulations.

[0013] Furthermore, in step 1, the preparation of the mineral powder sample to be tested includes pretreatment of the mineral powder sample to be tested, and the pretreatment is specifically as follows: first, the mineral powder sample to be tested is ground, passed through a 360-mesh sieve, and then dried in a constant temperature oven at 100-110°C for 60 minutes.

[0014] Furthermore, in step 1, the preparation of the mineral powder sample to be tested also includes the preparation of an XRD test sample, and the preparation of the XRD test sample is specifically as follows: 4 grams of the pretreated mineral powder sample to be tested is weighed, and a special press is used to press the tablet (pressure 30 tons, holding pressure 20 seconds) to obtain an XRD test sample.

[0015] Further, in step 2, the digital image processing of the diffraction spectrum is specifically as follows: first, Minerals, Inorganic, ICSD Patterns and ICSD Minerals are selected as retrieval sample libraries to search for the main phases, and the phases are selected according to the dI / I0 value and the matching factor. The matching factor is required to be less than 10, and the matching between the selected phase and the measured spectrum is checked. The unmatched peaks are re-searched by single peak analysis, and the specified element analysis function is used to assist the retrieval; then the relative mass percentage of each phase is calculated using the Quantitative module of the MDI Jade software.

[0016] Furthermore, in step 4, the digital image processing of the standard fluorescence spectrum and the measured fluorescence spectrum includes drawing of a standard image, and the specific operations are as follows: a standard limestone sample and a mineral powder sample to be tested are selected, and the X-ray fluorescence intensity of the characteristic spectral lines of the corresponding chemical components of the standard limestone sample and the limestone sample to be tested are respectively determined according to the main measurement conditions of the corresponding elements; with the measured fluorescence intensity as the ordinate and the known relative mass percentage of the chemical component as the abscissa, the standard working curve and the measured curve of the XRF test analysis of a certain chemical component in the standard limestone sample and the mineral powder sample to be tested are respectively obtained.

[0017] Furthermore, in step 4, the digital image processing of the standard fluorescence spectrum and the measured fluorescence spectrum also includes the selection of characteristic peak positions and the analysis of fluorescence intensity changes: the standard curve method is used to determine the position and intensity of the peak corresponding to each element in the fluorescence spectrum, and the fluorescence intensity and the relative mass percentage of the chemical component are related by the formula: I i =Q i ×C i / μ s Get the element concentration I i , and then determine the relative mass percentage W of the corresponding chemical composition according to the stoichiometric relationship between the element and the compound t %, of which I i Represents the fluorescence intensity of the element to be measured, μ s represents the sample mass absorption coefficient, C i represents the concentration of the element to be measured, Q i Represents the proportionality constant.

[0018] Furthermore, in step 4, the measured main element composition and chemical composition of the mineral powder sample to be tested are as follows: the main element composition includes calcium (Ca), magnesium (Mg), silicon (Si), etc., and the chemical composition includes calcium oxide (CaO), magnesium oxide (MgO) and silicon dioxide (SiO2).

[0019] Furthermore, in step 5, the measured effective mineral components of the mineral powder sample to be tested are specifically as follows: the effective mineral components include calcite, dolomite, and quartz.

[0020] Further, in step 5, the processing rock lithology of the mineral powder is determined according to the judgment standard as follows: taking the measured relative mass percentages of calcite, dolomite and quartz as indicators, the test results of the mineral powder sample to be tested are compared and analyzed with the mineral composition of the standard limestone sample to determine whether the rock lithology of the mineral powder is limestone.

[0021] Furthermore, in step 5, the judgment criteria are: the relative mass percentage of calcite is ≥50%, the relative mass percentage of quartz is ≤5%, and the relative mass percentage of dolomite is ≤15%.

[0022] Further, in step 6, the quality of the mineral powder sample to be tested is judged according to the standard provisions as follows: taking the types of chemical components corresponding to the main elements and their relative mass percentages as indicators, and the requirements of CaO relative mass percentage ≥50%; SiO2 relative mass percentage ≤5%; MgO relative mass percentage ≤5% in "Chemical Analysis Methods for Building Materials GB / T 176-2008", the quality of the mineral powder sample to be tested is evaluated by the relative mass percentage ratio; the chemical components are complete and the CaO content ratio is ≥1.1, and the MgO, SiO2 content ratio is ≤0.5, which is excellent; the chemical components are complete and the content ratio is ≥1.0 and <1.1, and the MgO, SiO2 content ratio is >0.5 and ≤1.0, which is qualified; the chemical components are incomplete or the CaO content ratio is <1.0 or the MgO, SiO2 content ratio is >1.0, which is unqualified.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention provides a method for quickly distinguishing limestone powder. Under the premise of not destroying the mineral powder sample to be tested, the diffraction spectrum and fluorescence spectrum of the mineral powder sample to be tested are respectively obtained by XRD method and XRF method, and the obtained diffraction spectrum and fluorescence spectrum are analyzed based on digital image processing technology to clarify the elemental composition, chemical composition, mineral composition and relative mass percentage of the mineral powder sample to be tested. The method has the advantages of short time consumption, high efficiency and high result accuracy, and can also lay a solid foundation for the subsequent limestone powder quality grading method. At the same time, it is convenient for quickly and accurately distinguishing whether the mineral powder on site is limestone powder and the quality of the mineral powder in the asphalt mixture production stage, thereby effectively realizing the effective supervision of the lithology of the processed rock, and is suitable for popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The present invention is a flowchart of a method for quickly distinguishing limestone powder.

[0026] Figure 2 It is the XRD diffraction pattern of the mineral powder sample to be tested. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In order to further understand the technical features of the present invention, the following is an example of a method for quickly identifying limestone powder. The specific steps are:

[0029] Step 1: prepare a mineral powder sample to be tested, and use an XRD device to perform X-ray diffraction on the prepared mineral powder sample to be tested to obtain a diffraction pattern.

[0030] The mineral powder sample to be tested was ground with a mortar and passed through a 360-mesh sieve. The sieved mineral powder sample was placed in a constant temperature oven at 100-110°C for drying for 60 minutes; 4 grams were weighed and prepared with a special press (pressure 30 tons, pressure holding 20 seconds); the prepared mineral powder sample to be tested was placed on the sample stage of the X-ray diffractometer, and after multiple adjustments, the optimal setting working parameters were obtained as follows: the scanning mode was continuous scanning (θ~2θ), the scanning angle range was 5~80°, the data point interval was 0.02°, the scanning speed was 3° / min, the working voltage was 40kV, the working current was 40mA, the filter combination, the scanning integration time was 400ms, and the scanning slice spacing was 1mm; under this scanning parameter, not only the scanning time can be shortened and the scanning efficiency can be improved, but also a higher quality diffraction spectrum can be obtained.

[0031] Step 2: Perform digital image processing on the diffraction spectrum to determine the type and relative mass percentage of effective mineral components in the mineral powder sample to be tested through characteristic peaks.

[0032] The present invention adopts MDI Jade 6.0 software to perform phase retrieval and quantitative analysis on the XRD diffraction peak spectrum of the mineral powder sample to be tested.

[0033] In order to complete the phase search, PDF-4+2022 cards were used as the search sample library to realize the phase search function. Since the measured samples were rock powders, four major database sub-libraries, namely Minerals, Inorganic, ICSD Patterns and ICSD Minerals, were selected. The search was mainly focused on the major phase (Search Focus on Major) and a selected peak (Search Focus on Painted) to retrieve the phase; select the phase according to the dI / I0 phase retrieval and PDF card selection principle. In the process of phase selection, if there are multiple cards of the same phase in the PDF library, select the phase with a smaller matching factor. Generally, the FOM value should be less than 10; the X-ray diffraction spectrum of limestone is shown in the figure. Through the search, it is found that the limestone mainly contains calcite, dolomite and quartz, among which calcite has peaks at scanning angles of 24.5°, 30.8°, 37.6°, 40.9°, 43.6°, 48.4°, 49.6° and 59.7°, dolomite has peaks at scanning angles of 32.0° and quartz has peaks at scanning angles of 27.4°. Then check the matching of the PDF card and the measured diffraction spectrum to determine whether there are any diffraction peaks that have not been detected; for the unmatched diffraction lines, use the single peak analysis function to re-search the phase, use the specified element analysis function to search the phase, and finally use the Quantitative function of the MDI Jade software to calculate its relative mass percentage Wt%.

[0034] Table 1 Limestone phase search results

[0035]

[0036] Table 2 Relative mass percentage of different phases

[0037]

[0038] Step 3: Use XRF technology to test the national standard material GBW03107A limestone sample and the mineral powder sample to be tested in turn to obtain the standard fluorescence spectrum and the measured fluorescence spectrum respectively.

[0039] There are two sample preparation methods for XRF analysis: melting and pressing. The melting method can eliminate the matrix effect of the sample and improve the analysis accuracy, but it is more expensive and takes longer. In addition, some components are easy to volatilize during the high-temperature melting process, which limits its application. The pressing method is simple to prepare samples, fast in analysis, relatively low in cost, and non-destructive in samples. It can better reflect the advantages of speed and simplicity in actual production and when the number of samples is large. It is widely used in XRF analysis of non-metallic mineral powder samples.

[0040] The present invention preferably uses a tabletting method to prepare XRF test samples. The pretreated sample is pressed into a cake-shaped sample and can be put on the machine for testing. The relevant parameters of the spectrometer are set according to the corresponding elements. The standard limestone sample is first measured and analyzed, the X-ray fluorescence intensity is recorded, and the standard fluorescence spectrum is obtained. Then, the same operation is performed on the mineral powder sample to be tested to obtain the measured fluorescence spectrum.

[0041] Table 3 Main measurement parameters of each element

[0042]

[0043] Step 4: Perform digital image processing on the standard fluorescence spectrum and the measured fluorescence spectrum, compare and analyze the position of the characteristic peak and the change of fluorescence intensity, and obtain information such as the main element composition, chemical composition and relative mass percentage of the measured mineral powder sample.

[0044] The conversion experiment of fluorescence intensity and relative mass percentage adopts the standard curve method; taking calcium oxide (CaO) as an example, the drawing method is: select the standard limestone sample and the mineral powder sample to be tested, and respectively measure the X-ray fluorescence intensity of the characteristic spectrum of calcium oxide (CaO) of the standard sample; use the measured calcium oxide (CaO) fluorescence intensity of each sample as the ordinate, and the known relative mass percentage of calcium oxide (CaO) of the standard sample as the abscissa to draw a scatter plot, that is, to obtain the calcium oxide (CaO) standard working curve for XRF test analysis of this type of sample. In the next step of testing and analyzing the relative mass percentage of the relevant chemical components in the mineral powder sample to be tested, it can be directly obtained from the standard working curve according to the X-ray fluorescence intensity value of the relevant chemical components measured by the sample to be tested.

[0045] Table 4 Relative mass percentage range of analyzed components in GBW03107A limestone sample

[0046]

[0047] The present invention preferably uses the standard curve analysis method to determine the position and intensity of the peak value corresponding to each element in the fluorescence spectrum. The fluorescence intensity and the relative mass percentage are expressed by the formula: I i =Q i ×C i / μ s Get the element concentration I i , and then determine the relative mass percentage of the corresponding chemical components according to the stoichiometric relationship between the elements and the compounds; where I i Represents the fluorescence intensity of the element to be measured, μ s represents the sample mass absorption coefficient, C irepresents the concentration of the element to be measured, Q i Represents the proportionality constant.

[0048] Table 5 Results of each component of standard limestone sample (W / %)

[0049] Table 6 Working curve regression results of the tested mineral powder samples

[0050] Table 7 Comparison of the results of each component in the mineral powder sample to be tested (W / %)

[0051]

[0052] Step 5: Using the measured effective mineral components and their relative mass percentages of the mineral powder sample to be tested as indicators, determine the lithology of the processed rock of the mineral powder according to the determination criteria.

[0053] The present invention preferably selects calcite, dolomite and quartz as indicators of effective mineral components, and compares and analyzes the differences between the relative mass percentages of calcite, dolomite and quartz in the mineral powder sample to be tested and the corresponding indicators of limestone. Only when the indicators are qualified can it be determined that the lithology of the processed rock of the mineral powder to be tested is limestone.

[0054] Table 8 Mineral composition test table of the mineral powder to be tested

[0055]

[0056] Step 6: Compare and analyze the chemical composition and relative mass percentage of the measured main elements of the mineral powder sample to be tested with the corresponding indicators of the standard limestone sample. According to the provisions of "Chemical Analysis Methods for Building Materials GB / T176-2008", the quality of the mineral powder to be tested is judged by the relative mass percentage ratio of the indicators.

[0057] The present invention preferably uses calcium (Ca), magnesium (Mg), silicon (Si) and the like as main elements, and calcium oxide (CaO), magnesium oxide (MgO) and silicon dioxide (SiO2) as chemical components corresponding to the main elements. According to the requirements of "Chemical Analysis Methods for Building Materials GB / T 176-2008" that the relative mass percentage of CaO is ≥50%; the relative mass percentage of SiO2 is ≤5%; and the relative mass percentage of MgO is ≤5%, the quality of the mineral powder to be tested is evaluated by the relative mass percentage ratio. The quality of the mineral powder to be tested is evaluated by the relative mass percentage ratio. The quality of the mineral powder to be tested is excellent if the chemical components are complete and the CaO content ratio is ≥1.1, and the MgO and SiO2 content ratio is ≤0.5. The quality of the mineral powder to be tested is qualified if the chemical components are complete and the content ratio is ≥1.0 and <1.1, and the MgO and SiO2 content ratio is >0.5 and ≤1.0. The quality of the mineral powder to be tested is unqualified if the chemical components are incomplete or the CaO content ratio is <1.0 or the MgO and SiO2 content ratio is >1.0.

[0058] Table 9 Chemical composition statistics of the mineral powder samples to be tested

[0059]

[0060] The XRD diffraction spectrum analysis results of the mineral powder to be tested showed that the mineral composition of the mineral powder included calcite, dolomite, quartz and carbon, and the relative mass percentages of the effective mineral components were 79.8% for calcite, 14.3% for dolomite and 3.3% for quartz, which were significantly higher than the judgment criteria. After multiple XRF analyses, it was shown that the chemical composition of the mineral powder was complete and the relative mass percentage ratio of CaO was between 1-1.1, the relative mass percentage ratio of MgO was between 0.1-0.5, and the relative mass percentage ratio of SiO2 was between 0.2-0.5. Therefore, it can be determined that the processed rock lithology of the mineral powder sample to be tested is limestone, and the quality of the mineral powder is of qualified grade.

[0061] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for rapid identification of limestone powder, characterized in that: The steps include: Step 1: prepare a mineral powder sample to be tested, and use an XRD device to perform X-ray diffraction on the prepared mineral powder sample to be tested to obtain a diffraction spectrum. Step 2: Perform digital image processing on the diffraction spectrum to determine the type and relative mass percentage of effective mineral components in the mineral powder sample to be tested through characteristic peaks. Step 3: Use XRF technology to test the national standard material GBW03107A limestone sample and the mineral powder sample to be tested in turn to obtain the standard fluorescence spectrum and the measured fluorescence spectrum respectively. Step 4: Perform digital image processing on the standard fluorescence spectrum and the measured fluorescence spectrum, compare and analyze the position of the characteristic peak and the change of fluorescence intensity, obtain the main element composition of the measured mineral powder sample, and use the main measurement parameters of the corresponding elements to determine the corresponding chemical composition and its relative mass percentage. Step 5: Using the measured effective mineral components and their relative mass percentages of the mineral powder sample to be tested as indicators, determine the processed rock lithology of the mineral powder sample to be tested according to the determination criteria. Step 6: Compare and analyze the chemical composition and relative mass percentage of the measured main elements of the mineral powder sample to be tested with the corresponding indicators of the standard limestone sample, and judge the quality of the mineral powder sample to be tested according to the standard regulations.

2. A method for rapid identification of limestone powder according to claim 1, characterized in that: In step 2 and step 5, the effective mineral components include calcite, dolomite and quartz.

3. A method for rapid identification of limestone powder according to claim 1, characterized in that: In step 4, the main element composition includes calcium (Ca), magnesium (Mg), silicon (Si), etc.

4. A method for rapid identification of limestone powder according to claim 1, characterized in that: In step 5, the judgment criteria are that the relative mass percentage of calcite is ≥50%, the relative mass percentage of quartz is ≤5%, and the relative mass percentage of dolomite is ≤15%.

5. The method for rapid identification of limestone powder according to claim 1, characterized in that: In step 6, the chemical composition is the same as the corresponding index of the standard limestone sample, including the relative mass percentages of calcium oxide (CaO), magnesium oxide (MgO) and silicon dioxide (SiO2), and the standard stipulates that the relative mass percentage of CaO is ≥50%; the relative mass percentage of SiO2 is ≤5%; the relative mass percentage of MgO is ≤5%; the chemical composition types are complete and the CaO content ratio is ≥1.1, and the MgO, SiO2 content ratio is ≤0.5, which is excellent; the chemical composition types are complete and the content ratio is ≥1.0 and <1.1, and the MgO, SiO2 content ratio is >0.5 and ≤1.0, which is qualified; the chemical composition types are incomplete or the CaO content ratio is <1.0 or the MgO, SiO2 content ratio is >1.0, which is unqualified.

Citation Information

Patent Citations

  • Electric blasting cap and ignition material for the same

    GB350036A

Cited By

  • Fluorite mine rapid identification and quantification method based on full spectrum fitting

    CN120820574A